Litterfall decomposition of coffee shaded with Tectona grandis or in full sun - Henrique, Nirvani S.; Maltoni, Katia L. [UNESP]; Faria, Glaucia A. [UNESP] (FapUNIFESP (SciELO), 2022)
Litterfall is an important source of soil nutrients, but its decomposition can be affected by the crop system used. The objective of this study was to evaluate litterfall decomposition and macronutrient stocks in coffee crop systems in shaded (SHCS) environments and those in full sun (FSCS). The experiment was conducted on a rural property in Cacoal, state of Rondônia, Brazil, in a 2 × 6 factorial scheme with two crop systems (SHCS and FSCS), and six litterfall decomposition evaluation times (0, 30, 60, 180, 300, and 360 days after the litterfall was returned to the soil (DAL)), with seven replicates. The constant of decomposition (k), half-life time (t1/2) at 360 DAL, and phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sulfur (S), and nitrogen (N) concentrations of the remaining litterfall were determined at each evaluation time. The litterfall in the SHCS had a greater weight loss and constant of decomposition and a lower half-life time at the last evaluation, and the weight loss increased as a function of decomposition time. The litterfall stocks of macronutrients N, P, K, Ca, and Mg showed a linear decrease throughout the decomposition time, and increases in sulfur stock were found at the last evaluation.
Decomposição de serapilheira de cafeeiro sombreado com Tectona grandis ou a pleno sol
Keywords: Coffea canephora; Litter bag; Shading; Sustainability